Beef Ban in India: A Multi-dimensional Issue - Khan, Anam; Riedel, Taylor; Hussain, Rabia; Patel, Isha (Journal of Pharmacy Practice and Community Medicine)
The Economic Times published an article in January 2019, highlighting the increasing problem of stray cattle in rural India. Four years ago, several states in India began making the decree to protect cows from slaughter at the end of their productive lives.[1] The largely Hindu population in India considers cows sacred and does not condone their slaughter. In 2012, there were only 5 million stray cattle roaming the Indian streets, but now there is an estimated 40 million unproductive cattle at risk of being abandoned.[1] India only has 5,000 shelters, each with a capacity of 200; but these are near enough.[1] Cattle are being abandoned because they are beyond the age of productivity and the cost for a farmer to keep an unproductive cow is Rs. 7500/month. Prior to the beef ban, farmers could sell dried up cows for Rs. 20,000 to Rs. 50,000 each depending on their age. Farmers are facing a severe economic deficit since they can no longer sell their cattle for profit.[1] The abundance of stray cattle has also led to Indians being physically attacked. Cows trespassing on farm land and destroying crops have recently led to them being locked up inside schools and hospitals for containment.[1] Currently, there is much controversy between Indian political parties on resolving the economic and social stress that cow abandonment has caused on several states in India.[2] There has been argument about the former cattle trade being important for the rural economy and necessary to provide revenue for dairy farmers unproductive cattle.[2]